2011
DOI: 10.1007/s11630-011-0446-9
|View full text |Cite
|
Sign up to set email alerts
|

Wind tunnel study on wind and turbulence intensity profiles in wind turbine wake

Abstract: In recent years, there has been a rapid development of the wind farms in Japan. It becomes very important to investigate the wind turbine arrangement in wind farm, in order that the wake of one wind turbine does not to interfere with the flow in other wind turbines. In such a case, in order to achieve the highest possible efficiency from the wind, and to install as many as possible wind turbines within a limited area, it becomes a necessity to study the mutual interference of the wake developed by wind turbine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 0 publications
3
16
0
Order By: Relevance
“…The sensor that was available to meet this objective was a single‐normal hot‐wire probe connected to a constant temperature hot‐wire anemometer. Single‐normal hot‐wire probes have been used by several authors to characterize the flow downstream of scaled wind turbines . The hot‐wire probe was manufactured by Auspex Scientific (Lehigh Valley, Pennsylvania) and had a 5 μm tungsten welded sensor with a length of 1 mm.…”
Section: Experimental Methodssupporting
confidence: 90%
“…The sensor that was available to meet this objective was a single‐normal hot‐wire probe connected to a constant temperature hot‐wire anemometer. Single‐normal hot‐wire probes have been used by several authors to characterize the flow downstream of scaled wind turbines . The hot‐wire probe was manufactured by Auspex Scientific (Lehigh Valley, Pennsylvania) and had a 5 μm tungsten welded sensor with a length of 1 mm.…”
Section: Experimental Methodssupporting
confidence: 90%
“…Evidence also shows that the turbulence level in the incoming flow affects the rate at which this velocity deficit decreases with downwind distance from the turbine (i.e., the wake recovery rate). In particular, both simulations [9][10][11] and experimental studies [6,[12][13][14] have shown that stand-alone turbine wakes recover faster in conditions of higher turbulence intensity levels in the incoming flows. This effect is found to affect the performance (power output) of the downwind turbines in large wind farms.…”
Section: Introductionmentioning
confidence: 99%
“…The turbulence intensity in the longitudinal direction TI and Reynolds numbers Re were defined as follows [13,14,16,23,31,35,41,42]:…”
Section: Turbulence Generationmentioning
confidence: 99%
“…Friction force acting on the blade surface was ignored. By using pressure measurement results, the lift and drag coefficients were computed according to the following equations [7,15,16,31,45]: …”
Section: Multiport Pressure Measurement Devicementioning
confidence: 99%
See 1 more Smart Citation